Confirmation of cardiomegaly from the cardiothoracic ratio post-mortem Lodox® imaging - Hofler, Rosemarie Ursula (Department of Pathology, 2019)
In post-mortem forensic radiology the cardiothoracic ratio (CTR) is seen as the most reliable and easiest method for the detection of an enlarged heart, where the maximum transverse diameter of the heart is divided by the maximum transverse diameter of the internal thoracic cage and if the result is greater than or equal to the 50 % threshold, the heart is deemed to be enlarged. This threshold is widely accepted and used in both clinical practice and in medicolegal post-mortem investigations. The primary aim of the study was to investigate the accuracy and reliability of this CTR threshold measured from the radiographs produced specifically by the Lodox Xmplar-dr scanner situated at the Forensic Pathology Service (FPS) Laboratory in Salt River, Cape Town, Western Cape. A secondary aim was to typify the observed enlarged heart, whether it was due to ventricle dilation or ventricle wall thickening leading to a diagnosis of cardiomegaly. The study was divided into a retrospective component which investigated past use of the CTR (%) in autopsy reports with regards to the cause of death/chief findings, at the Salt River FPS laboratory using the Division of Forensic Medicine and Toxicology, UCT, Office autopsies database, between years 2014 to 2016. The prospective component evaluated the reliability and accuracy of the CTR measured from conventional radiography produced by the Lodox scanner by comparing the diagnosis obtained from the CTR calculated from the Lodox images with the recorded heart weights. This CTR was also then compared to the CTR calculated with the heart in-situ in the pericardial sac to determine how accurate the radiograph produced from the Lodox scanner is for diagnosing an enlarged heart. The results showed a significant difference between the CTR calculated from the Lodox images versus the CTR calculated from the in-situ measurements, with the CTR from the Lodox images being better at detecting enlarged hearts, at 76 %, whereas the CTR calculated in-situ was better for detecting normal heart weights, at 84 %. Increasing the 50 % threshold would increase the specificity, thereby increasing the number of correctly identified normal heart weights as well as enlarged hearts, therefore a CTR threshold of 52 % (0.52) is recommended for the Lodox scanner for diagnosing an enlarged heart. When typifying the observed enlarged hearts the lack of mid-ventricular wall thickening together with the wall thinning suggests that the main cause of the CTR being over it 50 % threshold is dilation. It is important to note that in some of the cases the heart weight was still within the normal heart weight range.